Analysing Corruption in Public Investment in Vietnam: A Multiple-Government Official’s Survey - Ta, Jack; Nguyen, To Thanh (International Journal of Criminology and Sociology, 2021)
Three decades after the Renovation Period in 1986 (Doi Moi in Vietnamese), although Vietnam is a fully integrated member of the globalized capitalist economy, they are still facing several difficulties to anti-corruption as one of the most challenging concerns to communist party and government. Amongst of several types of corruption, our paper using corruption frequency in public investment in the Period 2009–2014 is to examine and evaluate effectiveness and accountabilities of anti-corruption in public investment in Vietnam. They include three main bodies, namely the Government Inspectorate of Vietnam, the People’s Procuracy of Vietnam and the People’s Public Security Forces of Vietnam. Using a survey questionnaire with 150 participants from three those agencies, this paper examines corruption and criminal behaviour in public investment in Vietnam as well as evaluates the effectiveness and accountabilities of anti-corruption in public investment in Vietnam. Current findings show the limited qualifications of anti-corruption officers affected the investigation of cases meanwhile offenders are often high-level and powerful officers that have greatly hindered the investigation of corruption cases in the field of public investment. Yet, lacking transparency in management little information on public investment projects available and its related monitors led to ideal conditions for corruption. Besides that, the provisions on the handling of responsibilities of heads of agencies, organisations or units when corrupt acts occur in their agencies, organisations or units are not yet specific and clear.